Community service experience among employees at Universiti Teknologi MARA, Cawangan Johor / Nur Aliah Abu Bakar - Abu Bakar, Nur Aliah (2014)
This study aims to examine the community service experience among employee. There were 169 questionnaire distributed at Universiti Teknologi Mara, Cawangan Johor. According to Autumn (1999) in Raskoff, A S., & Sundeen, A. R, (2000) said that after doing community service, employees get more experience whether positive or negative. Many people responded positively to the service or activities in community service program. They mostly liked the activities of service orientation and helping others, the opportunity for social interaction, a sense of accomplishment, and learning about careers, the community and themselves. The research design used the descriptive research. This study use the Statistical Package for the Social Science (SPSS) version 20.0 or data analysis. There are a few factor of employee involve in community service in this study which is how many community service that has involve, what the benefit that they get by involve in community service and how frequent they involve in community service. The respondent of this study were the staff of Universiti Teknologi Mara, Cawangan Johor. From the findings, it can be conclude that most of respondent are satisfied with the community service that they involve.